JAGUNG SEBAGAI MASKER TERHADAP KESEHATAN KULIT WAJAH KERING SECARA ALAMI - KHANSA, MUTHIA; Titin Supiani; Neneng Siti Silfi Ambarwati (Jurnal Tata Rias, 2019)
Advances in science and technology have significantly impacted cosmetic products, particularly those made with masks. Many people still believe that natural facial treatments are safer because they don't contain chemicals. Skin health is also a visible indicator of whether someone is young or old. Skin that has difficulty retaining water will become damaged and dry. Traditional beauty treatments utilize readily available natural ingredients, such as corn. Corn contains vitamins A, B, B1, C, E, and K, as well as carbohydrates, protein, and minerals, all of which are beneficial for skin health. Corn is a natural ingredient rich in these nutrients. This study aims to determine the effectiveness of corn as a mask for naturally improving dry facial skin health.